Age-dependent differences in DNA damage after in vitro CT exposure. (4th March 2018) - Gomolka, Maria; Oestreicher, Ursula; Rößler, Ute; Samaga, Daniel; Endesfelder, David; Lang, Peter; Neumaier, Klement; Belka, Claus; Niemeyer, Markus; Kiechle, Marion; Hasbargen, Uwe; Hübener, Christoph; et al.
Abstract: Purpose: Age dependent radiation sensitivity for DNA damage after in vitro blood exposure by computer tomography (CT) was investigated. Materials and methods: Radiation biomarkers (dicentrics and gammaH2AX) in blood samples of newborns, children under five years and adults after sham exposure (0 mGy), low-dose (41 mGy) and high-dose (978 mGy) in vitro CT exposure were analyzed. Results: Significantly higher levels of dicentric induction were found for the single and combined newborns/children group compared to adults, by a factor of 1.48 (95% CI 1.30–1.68), after exposure to 978 mGy. Although a significant dose response for damage induction and dose-dependent repair was found, the gammaH2AX assay did not show an age-dependent increase in DNA damage in newborns/children compared to adults. This was the case for the gammaH2AX levels after repair time intervals of 30 minutes and 24 hours, after correcting for the underlying background damage. For the low dose of 41 mGy, the power of the dicentric assay was also not sufficient to detect an age-dependent effect in the sample size investigated. Conclusion: A 1.5-fold increased level of dicentric aberrations is detected in newborns and children under five years after 1 Gy radiation exposure.